Millennial Generation Purchasing Behavior in Kupang: Tenun Ikat NTT - Maria Augustin Lopes Amaral (Indonesia Banking School, 2019)
Tenun Ikat NTT as traditional apparel hasn't attracted the youth market yet especially millennial genera-tion. The millennial generation is a potential market that profitable for Tenun Ikat NTT industry. This re-search tries to answer the questions about attitude and repurchase intention of the millennial generation to buy Tenun Ikat NTT. The author predicts positive attitude and positive norm subjective effect repurchase intention of millennial generation toward Tenun Ikat NTT. This research uses a non-random sampling method (convenience sampling) in order to collect data. One hundred ten young people in Kupang were used as respondents (born in 1982-2000). Data were collected using a questionnaire (google form). This study uses SEM analyze to test the data. The result suggested model fully conforms to theory reasoned ac-tion, attitude and subjective norm had effect toward repurchase intention, fashion involvement and product personality had an effect toward attitude. The study result could be taken to count any policies that link all of the characteristics used in this study.